2016
DOI: 10.4028/www.scientific.net/msf.880.140
|View full text |Cite
|
Sign up to set email alerts
|

Metallography &amp; Bulk Hardness of Artificially Aged Al6061-B<sub>4</sub>C-SiC Stir Cast Hybrid Composites

Abstract: Present investigation focusses on combined effect of B4C and SiC on the improvement in hardness with an average size of 35-40μm on Al6061 hybrid composite. Composites are produced by stir casting process. The effect of artificial aging treatment with different aging temperatures of 100, 150 and 200OC on the improvement in hardness is also investigated. Optical micrographs and Brinell hardness number have been discussed. An attempt is made to find out the intermetallic phase responsible for strengthening by Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…It was apparent that SiC and B4C particles in the Al6061 alloy accelerated the ageing kinetics compared to unreinforced alloy during age-hardening treatment. This is primarily due to the existence of areas with a large dislocation concentration between the matrix alloy and the reinforcement interface, which contributes to heterogeneous nucleation sites and a high diffusivity path for the precipitation of secondary rich precipitates [3,13,14]. Similar to Al6061 matrix alloy, HMMC is very profound to age hardening regardless of 100 or 200 °C temperature.…”
Section: Effect Of Reinforcement and Ageing Temperature On Hardness Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was apparent that SiC and B4C particles in the Al6061 alloy accelerated the ageing kinetics compared to unreinforced alloy during age-hardening treatment. This is primarily due to the existence of areas with a large dislocation concentration between the matrix alloy and the reinforcement interface, which contributes to heterogeneous nucleation sites and a high diffusivity path for the precipitation of secondary rich precipitates [3,13,14]. Similar to Al6061 matrix alloy, HMMC is very profound to age hardening regardless of 100 or 200 °C temperature.…”
Section: Effect Of Reinforcement and Ageing Temperature On Hardness Propertiesmentioning
confidence: 99%
“…Aluminium, copper, lead, magnesium, nickel, and titanium, and their alloys are significant non-ferrous metals and alloys. Age hardening is the prominent heat treatment process used to increase the specific strength of several aluminium alloys [1][2][3]. The primary purpose of ageing treatment of these alloys (Al-Mg-Si) is to obtain a systematically growing enormous number of uniformly distributed fine intermediate precipitates (Mg2Si) in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the increase in hardness of the composite was mainly owed to the existence of harder SiC and B 4 C particles in the matrix alloy, which act as obstacles to the dislocation motion. Sharma et al [21] examined the metallography and bulk hardness of artificially aged Al6061-B 4 C-SiC stir cast hybrid composites. A significant improvement in hardness, tensile strength, and a marginal decrease in ductility of hybrid composites were observed compared to aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The deposits from EN processes have high corrosion resistance, lower wear surface. They have a noticeable lower amount of porosity, which results in outstanding wearing off and the abrasion resistance of the thickness quotient (S. S. Sharma et al, 2016;Sánchez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%